The Problem of lnterference in Wireless Communications: The U.S. Regulatory "Solution" and the Property Rights Alternative - Viani, Bruno E. (2002)
The problem of interference in wireless communications was addressed in the U.S. by a command and control system instituted nearly eight decades ago. This system is currently applied in most countries that allow private investment inwireless communications. A brief analysis of how this system emerged in the U.S. and how it operates reveals its gross inefficiencies. An alternative approach based on property rights would be efficient not only in the allocation off requencies to its highest value use, but also in solving interference disputes. The cases of Guatemala and El Salvador, two adopters of this approach, illustrate the benefits of the latter system. Between 1997 and 2001, the annual growth rate of mobile telephony traffic in these two countries more than doubled the average for Latin America and was over 12 times that of Peru. Latin Americans may benefit substantially by abandoning the current command and control system modeled after the U.S. and embracing the property rights approach.